Persistent photoconductivity at LaVO3–SrTiO3 interface. (August 2020) - Goyal, Saveena; Singh, Ajit; Tomar, Ruchi; Kaur, Ripudaman; Bera, Chandan; Chakraverty, S.
Abstract: Light illumination is widely used to tune the electronic properties of semiconductors. We have studied the effect of temperature and wavelength of light on the photoconductivity and persistent photocurrent (PPC) on an insulating (3 unit cells (u.c.) of LaVO3 (LVO) on SrTiO3 (STO)) and a conducting (5 u.c. of LVO on STO) oxide interface. Photo induced insulator to metal transition has been observed for the insulating interface. For 405 nm wavelength light illumination, the conducting interface shows PPC at all temperatures, however for 532 nm wavelength light, it shows PPC state only above 220K. For insulating sample, PPC has been observed only for 405 nm light illumination above ~150K. A model band structure has been presented to understand the experimental observations. Highlights: For first time we have studied the photoconductivity at conducting and insulting interface of LaVO3 –SrTiO3. A light induced insulator to metal transition is observed at 76K for insulating sample. A crucial interplay between in-gap defect states, wavelength of light and temperature to realize PPC state is also studied. We have proposed possible band structure diagram and the mechanism that leads to PPC for both LaVO3 -SrTiO3 interfaces.